PENDAMPINGAN MATERI SIMPLE PAST TENSE MELALUI METODE GRAMMAR TRANSLATION METHOD PADA SISWA KELAS 8 DI MTS HIDAYATUL INSAN - Rahayu, Josilia Puspito; Qamariah, Zaitun; Syahid, Abdul (LPPM Universitas Flores, 2024)
Learning English is often challenging for junior high school students due to the limited usage of English in daily life, which can hinder their understanding of the subject matter. Learning activities are tasks undertaken by students in the learning process. Factors that can enhance learning activities include motivation provided by teachers to engage students actively in learning and the selection of appropriate and enjoyable teaching methods, one of which is the Grammar Translation Method (GTM). The challenge lies in creating effective and enjoyable learning environments, especially in teaching the simple past tense to eighth-grade students. The community service activity involving eighth-grade students was conducted on April 25, 2024, at Hidayatul Insan School. The activity aimed to strengthen simple past tense proficiency through the Grammar Target Method (GTM), covering three stages: preparation, implementation, and reporting. Implementing simple past tense using the Grammar Translation Method (GTM) for eighth-grade students at MTs Hidayatul Insan has proceeded smoothly and successfully. This is reflected in the high level of student enthusiasm during the learning process. With the implementation of this learning activity, it is hoped that the English language skills, particularly in the simple past tense topic, of eighth-grade students at MTs Hidayatul Insan will significantly improve in writing, reading, listening, and communication.